Indicators and policies to make work pay. Proceeding of the workshop organised by the European Commission - Carone, Giuseppe; Salomäki, Aino (Luxembourg, 2006)
"The Commission’s Directorate-General for Economic and Financial Affairs hosted a workshop on making-work-pay policies and indicators in March 2005, a particularly opportune moment to discuss these issues since it coincided with the new start for the Lisbon strategy with its increased focus on growth and jobs.